2021
DOI: 10.1016/j.yebeh.2021.108267
|View full text |Cite
|
Sign up to set email alerts
|

Healthy brain–muscle interface in epilepsy and COVID-19: Increased muscle effort is the alternative

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…We appreciate the opportunity to respond to this letter and thank Drs. Luiz Vancini, Santos Andrade, Knechtle, Theodoros Nikolaidis, and de Lira for their comments regarding our systematic review [1,2]. We reported that many articles (76.5%) did not describe any limitations concerning temporality when discussing the causality between psychological stress and seizure worsening in patients with epilepsy during the COVID-19 pandemic.…”
Section: To the Editormentioning
confidence: 99%
“…We appreciate the opportunity to respond to this letter and thank Drs. Luiz Vancini, Santos Andrade, Knechtle, Theodoros Nikolaidis, and de Lira for their comments regarding our systematic review [1,2]. We reported that many articles (76.5%) did not describe any limitations concerning temporality when discussing the causality between psychological stress and seizure worsening in patients with epilepsy during the COVID-19 pandemic.…”
Section: To the Editormentioning
confidence: 99%